Reasons for Exclusion of Apparently Healthy Mature Adult and Senior Dogs From a Clinical Trial - Gibbs, Nicole H.; Michalski, Hannah; Promislow, Daniel E. L.; Kaeberlein, Matt; Creevy, Kate E. (Frontiers in Veterinary Science, 2021)
Background– Interventional clinical trials intended to maintain health in aging dogs are unusual and require particular attention to exclusion criteria. Objectives – To describe reasons for exclusion when a mature adult canine population with normal health status was sought. Animals – 56 companion dogs nominated for a randomized controlled trial (RCT) Procedures – Exclusions occurred within Stage 1 (S1): owner-provided survey information; Stage 2 (S2): medical records review; and Stage 3 (S3): screening examination and within Owner, Dog, or Other factor categories. Results – Of 56 nominated dogs, 39 were excluded at S1 (n=19), S2 (n=5), and S3 (n=15), respectively. Dogs were excluded for Owner (n=4), Dog (n=27), Other (n=6), and concurrent (Owner + Dog; n=2) factors. The most common exclusion period was S1 (n=19), with weight outside the target range being the most common exclusion factor in that stage (n=10). Heart murmurs were the second most common exclusion factor (S1: n=1; S3: n=5); suspected or confirmed systemic illness was third most common (S1: n=2; S2: n=3; S3: n=2). Among dogs who passed S1 and S2 screening (n=32), 15 dogs (48%) were excluded at S3, for heart murmur > grade II/VI (n=5), cardiac arrhythmias (n=2), and clinicopathologic abnormalities (n=2). Conclusions – Dogs nominated for a clinical trial for healthy mature adult dogs were excluded for size, previous diagnoses, and newly discovered cardiac abnormalities. For future interventions in mature adult dogs of normal health status, it is important to define expected age-related abnormalities to ensure that meaningful exclusion criteria are used.